Effects of latticeQCD EoS and continuous emission on some observables - Hama, Y.; Andrade, R.; Grassi, F.; Socolowski, O.; Kodama, T.; Tavares, B.; Padula, S. S. [UNESP]; Simak, V; Sumbera, M.; Todorova, S.; Tomasik, B. (Amer Inst Physics, 2006)
Effects of lattice-QCD-inspired equations of state and continuous emission on some observables are discussed, by solving a 3D hydrodynamics. The particle multiplicity as well nu(2) are found to increase in the mid-rapidity. We also discuss the effects of the initial-condition fluctuations.
Keywords: latticeQCD equations of state; hydrodynamic model